Analisis Kualitas Pelayanan Mobile Banking Terhadap Kepuasan Nasabah Bank BSI KCP Imam Bonjol Meulaboh - Laila Rohana; Amsal Irmalis; Muzakkir, Muzakkir (MAMEN: Jurnal Manajemen, 2024)
The development of information and communication technology requires the banking industry to compete tightly in product innovation and electronic banking services. BSI Mobile banking has experienced complaints from people throughout Indonesia. Then, to overcome this problem, BSI informed that system maintenance was being carried out on the e-Channel service and it would return to normal. This research was studied to determine customer satisfaction so that the bank can improve the quality of BSI KCP Imam Bonjol Meulaboh Mobile Banking services, using concepts or ideas (Cronin & Taylor, (1994) to measure customer perceptions of service quality, five dimensions were used, namely tangible (physical evidence), reliability (reliability), responsiveness (responsiveness), assurance (insurance) and empathy (empathy). This research method, namely a quantitative research method. The results of this research explain that There are two variables that have a significant effect on customer satisfaction, and there are three variables that have no effect on mobile banking customer satisfaction at BSI KCP Imam Bonjol Meulaboqmaqlevel of satisfaction of mobile banking customers at BSI KCP Imam Bonjol Meulaboh are reliability, assurance and emphty.